The impact of time management on the performance of the functional business: Survey study at Al Salam General Company for Communications and Information Technology - احمد سالي ابراهيم (Journal of Economics and Administrative Sciences, 2020)
The aim of the research is to know the level of time management application and its impact on the performance of the job, a survey search in the general company for communication and information technology and provide recommendations that help employees to optimize the use of time and improve performance, which is an important element in controlling the various functions of the company. In order to achieve the objectives of the research, the questionnaire was based on two main variables and distributed to a random sample of (44) employees in the company out of (308) employees, thus the proportion of the sample (14%). After collecting the samples from the sample, there are (6) incomplete forms that have been retrieved because they are not valid for statistical analysis and to become the number of forms (44) form. Some statistical methods such as (arithmetic mean, standard deviation, and relative importance) were used to find out the perception of the sample individuals towards the research variables, and to test the validity of the hypotheses. The statistical program (s.p.s.s ver.21), which is used in the correlation test and the effect between the main and sub-variables of the research, was used to test the validity of the hypotheses. And by adopting the simple linear regression coefficient used to test the effect of time management and its dimensions of (planning and organization) on the explanatory variable (performance of the functional work). Finally, the research concluded that the most important results were a strong correlation and influence between time management and job performance.